Controlling the Dynamics of Cell Transition in Heterogeneous Cultures using Surface Chemistry. Issue 4 (13th November 2014) - Hickman, Graham J.; Rees, Robert C.; Boocock, David J.; Pockley, A. Graham; Perry, Carole C.
Abstract : Developing materials that can preferentially select defined cancer cell populations for biological characterization will greatly enhance our understanding of cancer cell growth, differentiation, and invasion. The transitional events between epithelial and mesenchymal phenotypes are particularly crucial, as primary tumors and secondary metastasis are generally epithelial in nature, whereas circulating mesenchymal cells derived from primary epithelial cells appear to facilitate the spread of disease and its resistance to therapy. This study describes an amino‐functionalized material, which promotes the enrichment of an epithelial phenotype from a single cell line containing both epithelial and mesenchymal subpopulations of cancer cells. The isolation and transitional control of such subpopulations using functional materials will advance understanding of the disease process, have a significant impact on the downstream development of new targeted cancer therapeutics, and also be applicable to tissue engineering and regenerative medicine. Abstract : An amino‐functionalized tissue culture material, which promotes enrichment of an epithelial phenotype from a cancer cell line containing both epithelial and mesenchymal subpopulations, is described. Transitional events in culture between epithelial and mesenchymal phenotypes are implicated in metastasis, isolation, and transitional control of such subpopulations using functional materials will enhance the understanding of cancer cell growth, differentiation, and invasion.